2017
DOI: 10.1038/npp.2017.236
|View full text |Cite
|
Sign up to set email alerts
|

R-Baclofen Reverses Cognitive Deficits and Improves Social Interactions in Two Lines of 16p11.2 Deletion Mice

Abstract: Human chromosome 16p11.2 microdeletion is among the most common gene copy number variations (CNVs) known to confer risk for intellectual disability (ID) and autism spectrum disorder (ASD) and affects an estimated 3 in 10 000 people. Caused by a single copy deletion of ~27 genes, 16p11.2 microdeletion syndrome is characterized by ID, impaired language, communication and socialization skills, and ASD. Studies in animal models where a single copy of the syntenic 16p11.2 region has been deleted have revealed morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 47 publications
7
84
3
Order By: Relevance
“…The Social Approach Task is one of the most widely utilized behavioral assays for investigation of mouse models of liability factors associated with autism spectrum disorders (ASD) (Bader et al, 2011; Chadman et al, 2008; Copping et al, 2017; Dougherty et al, 2013; Feyder et al, 2010; Grabrucker, Boeckers, & Grabrucker, 2016; Lugo, Swann, & Anderson, 2014; Maloney et al, 2018; Page, Kuti, Prestia, & Sur, 2009; Penagarikano et al, 2015; Samaco et al, 2012; Schwartzer et al, 2013; Stoppel et al, 2018; Won et al, 2012) The use of the Social Approach Task has both helped identify ASD liability models with good face validity, and advanced our understanding of the circuitry underlying social approach deficits. Unlike reciprocal social interaction assays requiring manual scoring, the Social Approach Task is automated, making it ideal for mechanistic studies that require several experiments with different interventions or genetic models.…”
Section: Introductionmentioning
confidence: 99%
“…The Social Approach Task is one of the most widely utilized behavioral assays for investigation of mouse models of liability factors associated with autism spectrum disorders (ASD) (Bader et al, 2011; Chadman et al, 2008; Copping et al, 2017; Dougherty et al, 2013; Feyder et al, 2010; Grabrucker, Boeckers, & Grabrucker, 2016; Lugo, Swann, & Anderson, 2014; Maloney et al, 2018; Page, Kuti, Prestia, & Sur, 2009; Penagarikano et al, 2015; Samaco et al, 2012; Schwartzer et al, 2013; Stoppel et al, 2018; Won et al, 2012) The use of the Social Approach Task has both helped identify ASD liability models with good face validity, and advanced our understanding of the circuitry underlying social approach deficits. Unlike reciprocal social interaction assays requiring manual scoring, the Social Approach Task is automated, making it ideal for mechanistic studies that require several experiments with different interventions or genetic models.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence indicate that targeting various GABA receptor subtypes and allosteric modulatory sites may ameliorate autism‐relevant phenotypes in mouse models of autism. These include our previous reports that a GABA‐B agonist, r‐baclofen, improved social behaviors and reduced repetitive behaviors in BTBR and C58/J mice [Silverman et al, ], and improved social and cognitive deficits in 16p11.2 deletion mice [Stoppel et al, ], and several reports that low doses of benzodiazepines ameliorated autism‐relevant behavioral symptoms in BTBR [Pobbe et al, ; Defensor et al, ; Han et al, ; Yoshimura et al, ]. Therapeutics that increase GABAergic neurotransmission offer potential targets for treating symptoms of autism [Lemonnier et al, ; Erickson et al, ; Mohler, ; Veenstra‐VanderWeele et al, ], particularly in individuals with debilitating repetitive behaviors, seizures, unusual profiles of EEG physiology, mutations in GABA receptor genes, mutations which reduce the development or functions of GABAergic interneurons, and other indicators of impaired inhibitory neurotransmission.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous studies with B6, BTBR, and Shank3B had revealed similar scores in males and females on the behavioral assays used in the present studies [Yang et al, 2007;McFarlane et al, 2008;Silverman et al, 2012Silverman et al, , 2015Kazdoba et al, 2016a;Dhamne et al, 2017], therefore both males and females were approximately equally represented in the Ns for each cohort, with the exception of male-female reciprocal social interactions in which only the males were tested. Breeding were designed to yield N = 12-15 per treatment group, to provide sufficient power to detect drug effects, as confirmed in previous studies [Silverman et al, 2012Silverman, Oliver, Karras, Gastrell, & Crawley, 2013;Kazdoba et al, 2016b;Stoppel et al, 2018]. Inconsistent Ns within a cohort across a testing sequence were the result of occasional cases of equipment failures, injection errors, and unexplained deaths.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…We only used the ( R )‐enantiomeric forms of all the compounds in this study, because this is the active enantiomer of Baclofen. Some bidirectional stereospecific assays of ( R )‐Baclofen and ( S )‐Baclofen have been reported in the literature, showing that ( R )‐Baclofen is more effective than ( S )‐Baclofen (Paredes & Agmo, ; Silverman et al., ; Stoppel et al., ). Additionally, ( S )‐Baclofen has shown an opposite biological effect in oral alcohol self‐administration assays compared with ( R )‐Baclofen (Lorrai, Maccioni, Gessa, & Colombo, ).…”
Section: Computational Detailsmentioning
confidence: 99%